2016
DOI: 10.1242/dev.138073
|View full text |Cite
|
Sign up to set email alerts
|

Complex cis-regulatory landscape of the insulin receptor gene underlies the broad expression of a central signaling regulator

Abstract: Insulin signaling plays key roles in development, growth and metabolism through dynamic control of glucose uptake, global protein translation and transcriptional regulation. Altered levels of insulin signaling are known to play key roles in development and disease, yet the molecular basis of such differential signaling remains obscure. Expression of the insulin receptor (InR) gene itself appears to play an important role, but the nature of the molecular wiring controlling InR transcription has not been elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 100 publications
(132 reference statements)
7
40
0
1
Order By: Relevance
“…Since enhancers can be used in a context-dependent manner (Nègre et al 2011;McKay and Lieb 2013;Wei et al 2016;Erceg et al 2017), we assessed whether DRREs are involved in other developmental events, regardless of their specific role in wing disc regeneration. We took advantage of chromatin accessibility data from different tissues and stages of fly development (McKay and Lieb 2013).…”
Section: A Specific Regeneration Regulomementioning
confidence: 99%
“…Since enhancers can be used in a context-dependent manner (Nègre et al 2011;McKay and Lieb 2013;Wei et al 2016;Erceg et al 2017), we assessed whether DRREs are involved in other developmental events, regardless of their specific role in wing disc regeneration. We took advantage of chromatin accessibility data from different tissues and stages of fly development (McKay and Lieb 2013).…”
Section: A Specific Regeneration Regulomementioning
confidence: 99%
“…The identification of the TFBSs contained in cis -regulatory elements constitutes the first step to elucidate the genetic and molecular mechanisms responsible for cis -regulatory divergence among species. We focused on the regulation of the InR gene transcription from its P2 promoter, despite that its transcript yield is much lower than from its P1 promoter, because a significant direct activation of P2 by dFOXO has been confirmed both in vitro and in vivo [ 7 , 16 ] whereas dFOXO also indirectly activates or represses additional enhancers located within introns of InR gene [ 7 ]. Previous band-shift studies had shown that in D .…”
Section: Discussionmentioning
confidence: 99%
“…Expression from the P1 promoter that drives the highest basal level of InR transcription was initially considered to be stable [ 6 ]. Recent work has, however, revealed that the regulation of InR expression from P1 is actually more complex as it is influenced by four intronic enhancers, with two of them activating transcription in response to dFOXO and the other two repressing it [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El gen que codifica para la insulina está localizado en el cromosoma 11p15. importante en la regulación de la transcripción del gen de insulina [43,44].…”
Section: Factores Transcripcionales Que Regulan La Expresión Del Gen unclassified